2022
DOI: 10.1001/jamanetworkopen.2022.29504
|View full text |Cite
|
Sign up to set email alerts
|

Association of Time-Based Billing With Evaluation and Management Revenue for Outpatient Visits

Abstract: IMPORTANCE Time-based billing options for physicians have expanded, enabling many physicians to bill according to time spent instead of medical decision-making (MDM) level for fee-for-service outpatient visits. However, no study to date has estimated the revenue changes associated with timebased billing. OBJECTIVE To compare evaluation and management (E/M) reimbursement for physicians using time-based billing vs MDM-based billing for outpatient visits of varying lengths. DESIGN, SETTING, AND PARTICIPANTS This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In the post- Dobbs period, females in states with these bans experienced the greatest loss of facility access. This study estimated that travel time to the nearest abortion facility in the state of Texas increased by almost a full workday (common US definition of 8 hours), highlighting the magnitude of the travel required to an abortion facility in the post- Dobbs period. Texas is a state that saw nearly 60 000 abortions per year in the pre- Dobbs period and had the highest rate of individuals without health insurance in the US …”
Section: Discussionmentioning
confidence: 99%
“…In the post- Dobbs period, females in states with these bans experienced the greatest loss of facility access. This study estimated that travel time to the nearest abortion facility in the state of Texas increased by almost a full workday (common US definition of 8 hours), highlighting the magnitude of the travel required to an abortion facility in the post- Dobbs period. Texas is a state that saw nearly 60 000 abortions per year in the pre- Dobbs period and had the highest rate of individuals without health insurance in the US …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the claims analyzed in this study occurred before the implementation of time-based billing for E/M coding in 2021, allowing physicians to include time spent before and after visits in coding calculations. 20 This argues that E/M coding at the time of these claims (2016-19) may have been more representative of patients' experience. However, future studies evaluating time toxicity and coding practices must also consider how time-based billing may alter future results, as it has been shown that physicians with longer visits are more likely to experience higher revenue when using time-based billing than physicians with shorter visits.…”
Section: Discussionmentioning
confidence: 99%
“…However, future studies evaluating time toxicity and coding practices must also consider how time-based billing may alter future results, as it has been shown that physicians with longer visits are more likely to experience higher revenue when using time-based billing than physicians with shorter visits. 20 This could indicate that endocrinologists with longer visit times than otolaryngologists may be more likely to use time-based billing more than their counterparts with shorter visit times on average, but differences in coding practices between specialties requires future study.…”
Section: Discussionmentioning
confidence: 99%